Detection of the SARS-CoV-2 spike protein in saliva with Shrinky-Dink© electrodes. Issue 7 (12th February 2021) - Zakashansky, Julia A.; Imamura, Amanda H.; Salgado, Darwin F.; Romero Mercieca, Heather C.; Aguas, Raphael F. L.; Lao, Angelou M.; Pariser, Joseph; Arroyo-Currás, Netzahualcóyotl; Khine, Michelle
Abstract : We introduce a simple, scalable, and portable electrochemical aptamer-based system for detection of the SARS-CoV-2 spike protein in saliva with attomolar sensitivity. Abstract : Using the children's toy, Shrinky-Dink©, we present an aptamer-based electrochemical (E-AB) assay that recognizes the spike protein of SARS-CoV-2 in saliva for viral infection detection. The low-cost electrodes are implementable at population scale and demonstrate detection down to 1 ag mL −1 of the S1 subunit of the spike protein.